An aqueous zinc ion battery electrolyte that can suppress side reactions and dendrites
By adding CTAB to the electrolytes of the zinc ion battery of the water system, the problem of side effects and branched crystal deterioration are solved, and the electrochemical properties and life of the battery are significantly improved.
Patent Information
- Application Number
- CN202311104249.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-08-30
AI Technical Summary
Water-based zinc ion batteries are prone to side reactions and dendrite deterioration during charging and discharging, limiting the electrochemical performance and life of the battery.
By adding hexisanelxyl tritenium bromide (CTAB) to the electrolyte, the surfactant can regulate the direction of zinc deposition, inhibit the growth of the branch crystal, and by destroying the solventive layer structure and water molecule of the ZN2+ The hydrogen bonding network is reduced to reduce the changes in hydrogen analysis and local pH.
Effectively suppress the deterioration of side effects and the deterioration of branches, improve the reversibility, safety and electrochemical properties of zinc ion batteries, and extend the life of the battery.
Smart Images

Figure HDA0004421553490000011 
Figure HDA0004421553490000012 
Figure HDA0004421553490000013
Abstract
Description
Technical Field
[0001] The invention relates to an aqueous zinc ion battery electrolyte capable of inhibiting side reactions and dendrites, and belongs to the field of aqueous zinc ion battery electrolyte additives. Background Art
[0002] Large-scale energy storage has become a necessity for the current social development. Energy plays an increasingly important role in people's lives. Therefore, it is particularly important to seek renewable energy. The development of secondary battery energy storage technology with excellent electrochemical performance and clean and environmentally friendly is inevitable in the face of the rapid upgrading of today's electronic products. Lithium-ion batteries (LIBs) have the advantages of high cycle life, high energy density, and mature technology. They are widely used in new energy vehicles and portable electronic devices. However, with the over-exploitation of lithium mines and resource shortages, the cost of LIBs is getting higher and higher. Unlike lithium-ion batteries, aqueous zinc-ion batteries have similar electrochemical properties to lithium-ion batteries due to their rich zinc resources, which has stimulated people's interest in zinc-ion batteries. Aqueous zinc-ion battery electrolytes have great advantages over organic electrolytes in terms of environmental protection, price, and safety. However, frequent side reactions and severe dendrite deterioration have limited the development of aqueous zinc-ion batteries. Therefore, it is crucial to study aqueous zinc-ion battery electrolytes that can inhibit side reactions and dendrites. Summary of the invention
[0003] In view of the above problems of the prior art, the present invention provides an aqueous zinc ion battery electrolyte that can inhibit side reactions and dendrites, aiming to improve the electrochemical performance and life of the battery.
[0004] In order to achieve the purpose, the present invention adopts the following technical scheme:
[0005] An aqueous zinc ion battery electrolyte capable of inhibiting side reactions and dendrites is characterized in that the aqueous zinc ion battery electrolyte comprises zinc sulfate ZnSO4, deionized water and hexadecyltrimethylammonium bromide CTAB. Hexadecyltrimethylammonium bromide (CTAB) is a surfactant that can be adsorbed on the surface of the zinc negative electrode to regulate the direction of zinc deposition. In addition, CTAB + On the surface of the zinc negative electrode, the electrostatic effect can slow down the zinc deposition behavior, thereby inhibiting the growth of dendrites. CTAB can also destroy Zn in the form of contact ion pairs. 2+ The stable solvation layer structure of the six surrounding water molecules destroys the original hydrogen bond network between water molecules, and reduces the hydrogen evolution reaction during the charge and discharge process by reducing the activity of water, thereby avoiding the change of local pH value and the generation of by-products. The electrolyte using CTAB additive for negative electrode protection of aqueous zinc-ion batteries can obtain excellent electrochemical properties such as longer life and higher safety.
[0006] Preferably, the concentration of ZnSO4 in the electrolyte is 0.5-2M.
[0007] Preferably, the concentration of CTAB in the electrolyte is 0.1-0.4 M, and most preferably 0.2 M. The present invention controls the content of CTAB to regulate the concentration of Zn in the electrolyte system. 2+ The solvation layer structure of Zn 2+ The surrounding coordinated water is reduced, inhibiting the Zn 2+ The side reactions of the nucleation process occur (such as the precipitation of H2 causing the local pH value to increase and the formation of the by-product Zn4SO4(OH)6·xH2O). The higher the content of CTAB in the electrolyte system, the better the effect of destroying the hydrogen bonds between water. 2+ The greater the change in the solvation structure, the more effective it is in suppressing the occurrence of side reactions. In addition, the adsorption layer of CTAB on the surface of the zinc sheet can act as an electrostatic shielding layer to suppress the "tip effect" and prevent the serious deterioration of zinc dendrites. The adsorption layer of CTAB on the surface of the zinc sheet can also effectively regulate the Zn 2+ The deposition direction of Zn 2+ Can be deposited along the (002) crystal plane, avoiding a large amount of Zn 2+ Deposited vertically on the surface of the zinc sheet, making Zn 2+ The deposition is denser and flatter, which effectively solves the problem of zinc dendrite deterioration. However, the adsorption layer of CTAB will increase the overpotential of zinc deposition, and when the CTAB content increases to a high enough level, the viscosity of the electrolyte will increase, and even lose the fluidity of the liquid. Therefore, it is very important to adjust the electrolyte suitable for zinc nucleation by adjusting the appropriate CTAB content.
[0008] The invention discloses a water-based zinc ion battery electrolyte capable of inhibiting side reactions and dendrites. The water-based zinc ion battery electrolyte is prepared by adding CTAB to a prepared zinc sulfate solution, and then stirring and ultrasonicating the solution until the mixture is uniformly mixed, thereby obtaining the water-based zinc ion battery electrolyte.
[0009] The present invention further provides an aqueous zinc ion battery, which uses the aqueous zinc ion battery electrolyte.
[0010] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0011] 1. The aqueous zinc ion battery electrolyte of the present invention contains CTAB, which can break down Zn 2+ The reversibility and safety of zinc-ion batteries are comprehensively improved by improving the solvation layer structure, breaking the hydrogen bond system between water molecules, adsorbing on the surface of zinc foil to regulate the direction of zinc deposition, inhibiting the deterioration of zinc dendrites, adjusting the appropriate voltage hysteresis, and other aspects to achieve excellent electrochemical performance.
[0012] 2. The electrolyte containing CTAB additive of the present invention adopts conventional medicines, has a simple preparation method, is easy to mass produce, and uses cheap and readily available raw materials. It is applied to aqueous zinc ion batteries and shows good reversibility and high safety, and has excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 These are electronic photographs of the electrolytes obtained in Examples 1-4 of the present invention and Comparative Example 1.
[0014] Figure 2 It is the pH value of the electrolyte obtained in Comparative Example 1 and Examples 1-3 of the present invention.
[0015] Figure 3 It is the ionic conductivity of the electrolyte obtained in Comparative Example 1 and Examples 1-3 of the present invention.
[0016] Figure 4 The Raman spectra of the electrolytes obtained in Comparative Example 1 and Examples 1-3 of the present invention are shown.
[0017] Figure 5 The Zn / Zn symmetric battery assembled with the electrolytes obtained in Comparative Example 1 and Examples 1-3 of the present invention at a current density of 1 mA cm -2 、Area capacity 0.5mAh cm -2 The cycle performance diagram below.
[0018] Figure 6 The Zn / Zn symmetric battery assembled with the electrolytes obtained in Comparative Example 1 and Examples 1-3 of the present invention was subjected to a current density of 2 mA cm -2 、Area capacity 1mAh cm -2 The cycle performance diagram below.
[0019] Figure 7 The Zn / Cu battery assembled with the electrolytes obtained in Comparative Example 1 and Example 2 of the present invention was tested at a current density of 0.4 mA cm -2 、Area capacity 0.2mAh cm -2 Cyclic Coulomb efficiency diagram below.
[0020] Figure 8 The Zn / Cu battery assembled with the electrolyte obtained in Example 1 of the present invention was -2 、Area capacity 0.2mAh cm -2 Cyclic Coulomb efficiency diagram below.
[0021] Fig. 9 The Zn / Cu battery assembled with the electrolyte obtained in Example 3 of the present invention was -2 、Area capacity 0.2mAh cm -2 Cyclic Coulomb efficiency diagram below.
[0022] Fig.10 The Zn / Cu battery assembled with the electrolytes obtained in Comparative Example 1 and Example 2 of the present invention was tested at a current density of 1 mA cm -2 、Area capacity 0.5mAh cm -2 Cyclic Coulomb efficiency diagram below.
[0023] Fig.11 The Zn / Cu battery assembled with the electrolyte obtained in Example 1 of the present invention was -2 、Area capacity 0.5mAh cm -2 Cyclic Coulomb efficiency diagram below.
[0024] Fig.12 The Zn / Cu battery assembled with the electrolyte obtained in Example 3 of the present invention was -2 、Area capacity 0.5mAh cm -2 Cyclic Coulomb efficiency diagram below.
[0025] Fig.13 This is a digital photograph of the zinc electrode of the Zn / Zn symmetrical battery assembled with the electrolytes obtained in Comparative Example 1 and Example 2 of the present invention after cycling.
[0026] Fig.14 This is a SEM image of the zinc electrode of a Zn / Zn symmetrical battery assembled with the electrolyte obtained in Comparative Example 1 of the present invention after cycling.
[0027] Fig.15 This is a SEM image of the zinc electrode of the Zn / Zn symmetric battery assembled with the electrolyte obtained in Example 2 of the present invention after cycling.
[0028] Fig.16 This is a digital photograph of zinc electrodeposited on Cu foil using the electrolytes obtained in Comparative Example 1 and Example 2 of the present invention.
[0029] Fig.17 This is a SEM picture of zinc electrodeposited on Cu foil from the electrolyte obtained in Comparative Example 1 of the present invention.
[0030] Fig.18 This is a SEM picture of zinc electrodeposited on Cu foil from the electrolyte obtained in Example 2 of the present invention.
[0031] Fig.19 This is a SEM image of the MnO2 positive electrode material used when the electrolytes of Comparative Example 2 and Example 5 of the present invention are assembled into zinc-manganese batteries.
[0032] Fig. 20 This is the XRD spectrum of the MnO2 positive electrode material used when the electrolytes of Comparative Example 2 and Example 5 of the present invention are assembled into zinc-manganese batteries.
[0033] Fig.21 The zinc-manganese battery assembled with the electrolyte of Comparative Example 2 and Example 5 of the present invention is 1Ag -1 Cycling capacity performance diagram at different current densities. DETAILED DESCRIPTION
[0034] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.
[0035] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0036] Unless otherwise specified, the reagents and materials used in the following examples can be obtained from commercial sources.
[0037] The battery performance tests in the following embodiments all adopt the Xinwei battery testing system, and the assembled batteries include:
[0038] Zn / Zn symmetric battery: zinc foil is used as positive and negative electrodes, glass fiber membrane is used as separator, and the electrolyte is the electrolyte configured in Examples 1 to 4 or Comparative Example 1. The Zn / Zn symmetric battery is assembled into a 2032 button cell in an air atmosphere. Test the Zn / Zn symmetric battery at different current densities (mAcm -2 ) and areal capacity (mAh cm -2 ), which proves that the CTAB additive can guide the zinc ions to deposit evenly on the surface of the negative electrode zinc sheet.
[0039] Zn / Cu half-cell: zinc foil is used as the negative electrode, copper foil is used as the positive electrode, glass fiber membrane is used as the separator, and the electrolyte is the electrolyte configured in Examples 1 to 4 or Comparative Example 1. The battery is assembled into a 2032 button cell in an air atmosphere. Test Zn / Cu half-cell at different current densities (mAcm -2 ) and areal capacity (mAh cm -2 ) and the effect of CTAB on the morphology of zinc ion deposition was investigated through data comparison.
[0040] Zn-MnO2 battery: MnO2, Ketjen black and PVDF were mixed in a mass ratio of 70:20:10 and uniformly dissolved in NMP solution to prepare a slurry, which was then uniformly coated on a titanium foil current collector to prepare a working electrode. A glass fiber separator was used, and the electrolyte was the electrolyte obtained in Example 5 or Comparative Example 2. A 2032 button cell was assembled in an air atmosphere, and the test voltage range was 0.8V-1.8V vs Zn / Zn 2+ .
[0041] Example 1
[0042] The aqueous zinc ion battery electrolyte of this embodiment contains 1M ZnSO4+0.1M CTAB (0.1M CTZB-ZS), and the specific preparation steps are as follows:
[0043] Step 1: Weigh 2.876 g of zinc sulfate into a beaker, add 6 mL of deionized water, stir for 10 min to dissolve, then add 0.364 g of CTAB, add deionized water to 10 mL, stir for 10 min, and ultrasonicate for 1 h until the solution is mixed evenly.
[0044] Step 2: Filter the solution obtained by sufficient stirring and ultrasonication to remove insoluble impurities, and obtain an aqueous zinc ion battery electrolyte containing 1M ZnSO4+0.1M CTAB, recorded as 0.1M CTZB-ZS.
[0045] Example 2
[0046] The aqueous zinc ion battery electrolyte of this embodiment contains 1M ZnSO4+0.2M CTAB (0.2M CTZB-ZS), and the specific preparation steps are as follows:
[0047] Step 1: Weigh 2.876 g of zinc sulfate into a beaker, add 6 mL of deionized water, stir for 10 min to dissolve, then add 0.728 g of CTAB, add deionized water to 10 mL, stir for 10 min, and ultrasonicate for 1 h until the solution is mixed evenly.
[0048] Step 2: Filter the solution obtained by sufficient stirring and ultrasonication to remove insoluble impurities, and obtain an aqueous zinc ion battery electrolyte containing 1M ZnSO4+0.2M CTAB, recorded as 0.2M CTZB-ZS.
[0049] Example 3
[0050] The aqueous zinc ion battery electrolyte of this embodiment contains 1M ZnSO4+0.3M CTAB (0.3M CTZB-ZS), and the specific preparation steps are as follows:
[0051] Step 1: Weigh 2.876 g of zinc sulfate into a beaker, add 6 mL of deionized water, stir for 10 min to dissolve, then add 1.092 g of CTAB, add deionized water to 10 mL, stir for 10 min, and ultrasonicate for 1 h until the solution is mixed evenly.
[0052] Step 2: Filter the solution obtained by sufficient stirring and ultrasonication to remove insoluble impurities, and obtain an aqueous zinc ion battery electrolyte containing 1M ZnSO4+0.3M CTAB, recorded as 0.3M CTZB-ZS.
[0053] Example 4
[0054] The aqueous zinc ion battery electrolyte of this embodiment contains 1M ZnSO4+0.4M CTAB (0.4M CTZB-ZS), and the specific preparation steps are as follows:
[0055] Step 1: Weigh 2.876 g of zinc sulfate into a beaker, add 6 mL of deionized water, stir for 10 min to dissolve, then add 1.456 g of CTAB, add deionized water to 10 mL, stir for 10 min, and ultrasonicate for 1 h until the solution is mixed evenly.
[0056] Step 2: Filter the solution obtained by sufficient stirring and ultrasonication to remove insoluble impurities, and obtain an aqueous zinc ion battery electrolyte containing 1M ZnSO4+0.4M CTAB, recorded as 0.4M CTZB-ZS.
[0057] Example 5
[0058] The aqueous zinc ion battery electrolyte of this embodiment contains 1M ZnSO4+0.2M CTAB+0.1M MnSO4, and the specific preparation steps are as follows:
[0059] Step 1: Weigh 2.876 g zinc sulfate and 0.169 g manganese sulfate in a beaker, add 6 mL deionized water, stir for 10 min to dissolve, then add 0.728 g CTAB, add deionized water to 10 mL, stir for 10 min, and ultrasonicate for 1 h until the solution is mixed evenly.
[0060] Step 2: Filter the solution obtained by sufficient stirring and ultrasonication to remove insoluble impurities, and obtain an aqueous zinc ion battery electrolyte containing 1M ZnSO4+0.2M CTAB+0.1M MnSO4.
[0061] Comparative Example 1
[0062] The aqueous zinc ion battery electrolyte of this comparative example contains only 1M ZnSO4, and the specific preparation steps are as follows:
[0063] Step 1: Weigh 2.876 g of zinc sulfate into a beaker, add 6 mL of deionized water, stir for 10 min to dissolve, add deionized water to 10 mL, stir for 10 min, and ultrasonicate for 1 h until the solution is mixed evenly.
[0064] Step 2: Filter the solution obtained by sufficient stirring and ultrasonication to remove insoluble impurities and obtain an aqueous zinc ion battery electrolyte containing 1M ZnSO4.
[0065] Comparative Example 2
[0066] The aqueous zinc ion battery electrolyte of this comparative example contains 1M ZnSO4+0.1M MnSO4, and the specific preparation steps are as follows:
[0067] Step 1: Weigh 2.876g zinc sulfate and 0.169g manganese sulfate in a beaker, add 6mL deionized water, stir for 10min to dissolve, add deionized water to 10mL, stir for 10min, and ultrasonicate for 1h until the solution is mixed evenly.
[0068] Step 2: Filter the solution obtained by sufficient stirring and ultrasonication to remove insoluble impurities, and obtain an aqueous zinc ion battery electrolyte containing 1M ZnSO4+0.1M MnSO4.
[0069] Figure 1 The electronic photos of the electrolytes containing different proportions of CTAB obtained in Comparative Example 1 and Examples 1-4 of the present invention clearly show that the electrolytes configured at each proportion are very uniformly dispersed and are all colorless and transparent. Except for Example 4, which has a high viscosity due to the excessively high CTAB content, the other examples all have good fluidity.
[0070] Figure 2 The pH values of the electrolytes obtained in Comparative Example 1 and Examples 1-3 of the present invention, a lower pH value will increase the corrosion rate of the zinc negative electrode, a higher pH value will increase the generation of alkaline by-products, and the electrolyte obtained in Example 2 of the present invention has a suitable pH environment for zinc deposition.
[0071] Figure 3 The ionic conductivity values of the electrolytes obtained in Comparative Example 1 and Examples 1-3 of the present invention are as follows. As the CTAB content increases, the ionic conductivity of the electrolyte gradually increases. The conductivity of Example 3 stops increasing due to viscosity, and Example 2 has a higher ionic conductivity.
[0072] Figure 4 The Raman spectra of the electrolytes obtained in Comparative Example 1 and Examples 1-3 of the present invention are shown in Figure 1. As the content of CTAB increases, the stretching vibration of OH undergoes a blue shift, indicating that the introduction of CTAB weakens the hydrogen bonding between water and water in the solution, breaks the original hydrogen bonding system of the solution, reduces the number of water molecules in the zinc ion solvation layer, and reduces the activity of water.
[0073] Figure 5 , Figure 6 The Zn / Zn symmetric cells assembled with the electrolytes obtained in Comparative Example 1 and Examples 1-3 of the present invention were -2 and 2mAh cm -2 Cycling performance diagram under current density. The Zn / Zn symmetric battery using the electrolyte containing CTAB additive shows better stability during cycling and has a greatly improved life. The battery assembled with the electrolyte obtained in Example 2 of the present invention has a high current density of 1 mA cm -2 and 2mAh cm -2The current density can be stably operated for more than 2500h and 2000h respectively.
[0074] Figure 7 , Figure 8 , Fig. 9 The Zn / Cu battery assembled with the electrolytes obtained in Comparative Example 1 and Examples 1, 2, and 3 of the present invention was tested at 0.4 mA cm -2 Current density (areal capacity 0.2 mAh cm -2 ) under cyclic coulombic efficiency. When the electrolyte contains CTAB additive, the Zn / Cu battery shows better stability and higher average coulombic efficiency during cycling. The electrolyte obtained in Example 2 of the present invention can maintain a high average coulombic efficiency of 99.43% for 2500 stable cycles.
[0075] Fig.10 , Fig.11 , Fig.12 The Zn / Cu battery assembled with the electrolytes obtained in Comparative Example 1 and Examples 1, 2, and 3 of the present invention was -2 Current density (areal capacity 0.5 mAh cm -2 ) under cyclic coulombic efficiency. When the electrolyte contains CTAB additive, the Zn / Cu battery shows better stability and higher average coulombic efficiency during cycling. The electrolyte obtained in Example 2 of the present invention can maintain a high average coulombic efficiency of 99.70% for 1000 stable cycles.
[0076] Fig.13 The Zn / Zn symmetric battery assembled with the electrolytes obtained in Comparative Example 1 and Example 2 of the present invention was -2 Digital photo of zinc electrode after 20 cycles at the current density. When using the electrolyte 0.2M CTAB-ZS obtained in Example 2, the corrosion degree of zinc foil surface is significantly lower than that of zinc electrode using the electrolyte 1M ZnSO4 obtained in Comparative Example 1.
[0077] Fig.14 The Zn / Zn symmetrical battery assembled with the electrolyte obtained in Comparative Example 1 of the present invention is -2 SEM image of zinc electrode after 20 cycles at the same current density. After cycling, the zinc electrode using 1M ZnSO4 electrolyte without CTAB additive had many sharp-edged zinc dendrites on its surface, uneven zinc deposition, and a very rough surface.
[0078] Fig.15 The Zn / Zn symmetric battery assembled with the electrolyte obtained in Example 2 of the present invention is -2SEM image of zinc electrode after 20 cycles at the same current density. The surface of the zinc electrode using 0.2M CTAB-ZS electrolyte remains flat after cycling, indicating that zinc deposition is very uniform and there are no obvious dendrites on the surface of the zinc electrode.
[0079] The electrolytes obtained in Comparative Example 1 and Example 2 were deposited on Cu foil by electrolytic cell electrodeposition, and the morphology of zinc deposition and SEM microscopic zinc ion deposition morphology were observed. Fig.16 The digital photos are of the morphology of zinc deposited on Cu foil by the electrolytes obtained in Comparative Example 1 and Example 2 of the present invention. The zinc deposited by the electrolyte of Example 2 is obviously flatter and denser than that by the electrolyte of Comparative Example 1. Fig.17 This is a SEM image of the zinc morphology deposited on the Cu foil from the electrolyte obtained in Comparative Example 1 of the present invention. The zinc deposition is disorderly and the surface is rough and loose. Fig.18 This is a SEM image of the zinc morphology deposited on the Cu foil from the electrolyte obtained in Example 2 of the present invention. The zinc deposit is flat, dense and orderly.
[0080] Fig.19 This is a SEM picture of the MnO2 positive electrode material used when the electrolytes of Comparative Example 2 and Example 5 of the present invention are assembled into zinc-manganese batteries, from which it can be clearly seen that nano-scale MnO2 is successfully prepared.
[0081] Fig. 20 This is the XRD spectrum of the MnO2 positive electrode material used when the electrolytes of Comparative Example 2 and Example 5 of the present invention are assembled into zinc-manganese batteries, from which the characteristic peaks corresponding to MnO2 can be clearly seen.
[0082] Fig.21 The zinc-manganese battery assembled with the electrolyte obtained in Comparative Example 2 and Example 5 of the present invention with or without CTAB additive is 1Ag -1 Cyclic performance diagram under current density. When the electrolyte obtained in Example 5 is used, at 1Ag -1 After 100 cycles at a current density of , the zinc-manganese battery can have a current density of 242.81 mAh g -1 The specific capacity is significantly better than that of the electrolyte obtained in Comparative Example 2.
[0083] In summary, the multifunctional electrolyte prepared by the present invention can significantly inhibit the deterioration of side reactions and dendrites when used for negative electrode protection of aqueous zinc ion batteries, and has excellent performance.
Claims
1. An aqueous zinc ion battery electrolyte capable of inhibiting side reactions and dendrites, characterized in that: The aqueous zinc ion battery electrolyte comprises zinc sulfate ZnSO4, deionized water and cetyltrimethylammonium bromide CTAB; the concentration of the ZnSO4 in the electrolyte is 0.5-2 M, and the concentration of the CTAB in the electrolyte is 0.2 M.
2. A method for preparing an aqueous zinc ion battery electrolyte according to claim 1, characterized in that: Add CTAB to the prepared zinc sulfate solution, and then stir and ultrasonicate until the mixture is uniformly mixed to obtain an aqueous zinc ion battery electrolyte.
3. An aqueous zinc ion battery, characterized in that: The aqueous zinc ion battery electrolyte according to claim 1 is used.
Citation Information
Patent Citations
Method for introducing cationic additive into electrolyte of zinc ion battery
CN115101832A